SISTEM INFORMASI DESA TIPANG BERBASIS WEB - Meliani Purba; Roni J. Simamora; Eva Julia G. Harianja (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2022)
The development of the village government is currently good with the village fun budget from the central government wich aims to advance the village, current village development cannot be separated from the support of information technology, almost every village requires information technology to improve services to the community. One example is the existence of an internet program entering the village, the internet is currently not only enjoyed by urban communities but has reached rural communities. The difficulty of accessing exiting information makes researchers interested in developing a website-based village information system with the aim of improving services to rural communities, access to information can be obtained easily, using interviews, field observations, and system design, this website-based information system can improve services to the public so that information to the public can be accessed easily and accurately.